Effect of the financial structure on the liquidity risk of SMEs in Cartagena as a base of project formulation (2023)
The Liquidity Risk in Small and Medium Enterprises - SMEs in the City of Cartagena-Colombia is analyzed, based on the determination of their Capital Structure. The variables, liquidity risk (dependent) and capital structure (independent), were analyzed, based on a quantitative investigation with a correlational approach. The hypothesis was, H1: There is a positive relationship between the capital structure and liquidity risk. The population came from the accounting database as of December 31, 2016 of the Superintendencia de Sociedades, with a sample of 260 companies. It is concluded that the higher the level of indebtedness, the greater the liquidity risk of the company tends to increase, thus accepting the hypothesis established in the investigation. Derived from the analysis presented, recommendations are offered on the formulation of projects that can contribute to the improvement of the liquidity conditions of the companies analyzed.